Agronomic performance and yield stability of yellow flax genotypes in the state of Santa Catarina, Brazil - Fioreze, Ana Carolina da Costa Lara; Konkol, Ana Caroline Basniak; Krassmann, Karol Anne; Orsi, Nicole; Parizotto, Cirio; Fioreze, Samuel Luiz (Pesquisa Agropecuaria Brasileira, 2024)
The objective of this work was to evaluate the performance and yield stability of yellow flax genotypes, as well as to identify the best ones for breeding. Nineteen lines and a local variety were cultivated in the 2018, 2019, and 2020 crop seasons in two environments (municipalities) in the state of Santa Catarina, Brazil. Number of capsules per plant, plant yield, grain yield, and final stand were determined. Data were analyzed across genotypes within each environment and across environments within genotypes. Genotype × environment interactions were evaluated by a joint analysis, in which stability and adaptability parameters were estimated. Correlations between final plant stand and yield components were also estimated. There is a high variability in the productive performance among genotypes. The genotype × environment interactions influenced plant traits. The effect of factors related to soil, climate, and population density on number of capsules and grain weight must be considered. The flax genotypes present high grain yield means in all environments. The analysis of stability and adaptability reveals that genotypes LINPG87 and LINPG88 stand out in productive performance and stability.